Forest refugia and riverine barriers promote diversification in the West African pygmy shrew (Crocidura obscurior complex, Soricomorpha). (5th September 2013) - Jacquet, François; Nicolas, Violaine; Colyn, Marc; Kadjo, Blaise; Hutterer, Rainer; Decher, Jan; Akpatou, Bertin; Cruaud, Corinne; Denys, Christiane
<x xml:space="preserve">Abstract</x> The Crocidura obscurior or West African pygmy shrew complex is endemic to West African forests from south‐eastern Guinea, eastern Liberia, southern Côte d'Ivoire and south‐western Ghana. We explore the genetic and morphometric diversity of 239 individuals of the C. obscurior complex from 17 localities across its geographical range. Using genetic data from three mitochondrial (16S, cytochrome b and COI) and four nuclear markers (BRCA1, STAT5A, HDAC2 and RIOK3) and skull geometric morphometrics, we show that this complex is composed of two cryptic and sympatric species, C. obscurior and C. eburnea. We then test several hypotheses to infer their evolutionary history. The observed phylogeographical pattern based on cytochrome b and COI sequences fits the forest refuge theory: during arid phases of the Plio‐Pleistocene, around 3.5, 2.1, 1 and 0.5 Mya, a small number of populations survived in isolated forest patches and diverged allopatrically. During wetter climatic periods, forests expanded, leading to secondary contacts between previously isolated populations. Our results also suggest the possible contribution of episodes of isolation in subrefuges. Historical variation of the West African hydrographic network could also have contributed to the observed patterns of genetic differentiation. Rivers such as the Volta and Sassandra may act as past and/or current barriers to gene flow. Although these two species have sympatric distributions, their phylogeographical histories are somewhat dissimilar due to small differences in their dispersal abilities and ecological requirements.